Evaluating differences in the Level of Working Conditions between the European Union Member States using TOPSIS method - Tutak, Magdalena; Brodny, Jarosław (Decision Making: Applications in Management and Engineering, 2022)
Work, which is a conscious activity of man, plays an immensely important role in their life and is the basis for the development of civilization. The work process is closely related to the conditions in which work is performed. These conditions include a number of social, technical, environmental as well as economic and organizational factors necessary to perform work safely in accordance with the applicable legal conditions. The role and importance of working conditions is appreciated by all organizations, countries and their groups taking action to improve them, including formal order. Given the importance and topicality of this issue, research has been carried out, the main goal of which was to assess the level of working conditions in the European Union (EU) countries according to the adopted criteria. The research was based on data from the European Foundation for the Improvement of Living and Working Conditions (Eurofound). Accordingly, eight main criteria were adopted, which were characterized by 64 sub-indicators. Such a broad approach to describing individual areas related to working conditions made it possible to analyze many factors influencing them. The research covered the 27 EU member states by determining indicators for working conditions criteria and an indicator for general (overall) working conditions. On this basis, their ranking and the level of working conditions in these countries were specified. The TOPSIS method was applied to this part of the research. With the use of partial levels of working conditions evaluation criteria and the k-means method, the authors identified countries similar in terms of the level of studied working conditions criteria. Based on the Spearman’s rho and Kendall’s Tau correlation coefficients, relationships were examined between the working conditions and the level of economic development and indicators characterizing the area of health and safety at work in the countries under study, which is very important from the point of view of working conditions. The results showed significant differences in working conditions between the EU-27. They were found to be definitely worse in the economically less developed countries (mainly the so-called "new" EU) than in the economically stronger states (the so-called "old" EU countries). The assessment and groups of similar countries in terms of working conditions should be used to develop strategies to improve these conditions in the EU-27. This is particularly significant in the context of dynamic technological, social and geopolitical changes across Europe, which have a significant impact on the labor market.